Un siglo de matrimonio en México - Quilodrán, Julieta (Centro de Estudios Demográficos Y de Desarrollo Urbano, Colegio de México, 2001)
Marriage constitutes, without a doubt, one of the foundations of social organization. Whichever modality it acquires, the sanction it grants gives legitimacy to one of the most important vital transitions in the life of individuals: the entry into marital life and, with it, the creation of a new unit, the family. . Thus, to the importance that this act has for the spouses individually, its social relevance is added from the moment that it creates a new space for the biological and social reproduction of the system. This book addresses some of the most relevant aspects of the nuptiality phenomenon from the perspective of classical demographic analysis.